Novel level shifter based physical unclonable function circuit design - Lijuan HAN; Lei QIAN; Enyi YAO; Xin LOU; Yuan CAO; Yanhua LIU (网络与信息安全学报)
Level shifters are widely used in low-power, multi-threshold integrated circuit chips.A novel physical unclonable function (PUF) design based on cross-coupled level shifter was proposed.In this work, a single switching transistor was inserted in the level shifter, which was the only overhead per response bit to change the operation mode of the cross-coupled level shifter from differential to common.The signature of the PUF was extracted while in common mode, by exploiting the uncertainty of the output voltage due to the difference of the switching time of the two PMOS in the cross-coupled network.Simulated with a standard 65 nm CMOS process, the results show the proposed PUF can produce a uniqueness of 49.11% and a reliability of 96.09% with the power supply voltage ranged from 1.0 V to 1.5 V and 95.31% with the temperature ranged from -20 ℃ to 100 ℃.The energy per bit is only 0.72 pJ at a high throughput of 20 Mbit/s (1.2 V, 27 ℃).